2020
DOI: 10.3390/mi11060605
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Analysis of Metal Adhesion to Parylene Polymer Substrate Using Scotch Tape Test for Peripheral Neural Probe

Abstract: This paper presents measurement and FEM (Finite Element Method) analysis of metal adhesion force to a parylene substrate for implantable neural probe. A test device composed of 300 nm-thick gold and 30 nm-thick titanium metal electrodes on top of parylene substrate was prepared. The metal electrodes suffer from delamination during wet metal patterning process; thus, CF4 plasma treatment was applied to the parylene substrate before metal deposition. The two thin film metal layers were deposited by e-beam evapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Moreover, the sheet resistance ( R s ) of the fabricated electrodes was measured using a 4-point probe system (Jandel, RM3-AT) at a constant current of 100 mA. The Scotch (3M magic tape) tape test method was applied to investigate the adhesion strength of the metallized layers . Besides, the ASTM D3359-02 standard tape test and ASTM D4541 pull-off adhesion test were conducted to quantify the interfacial adhesion strength between the deposited metal film and the polymer substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the sheet resistance ( R s ) of the fabricated electrodes was measured using a 4-point probe system (Jandel, RM3-AT) at a constant current of 100 mA. The Scotch (3M magic tape) tape test method was applied to investigate the adhesion strength of the metallized layers . Besides, the ASTM D3359-02 standard tape test and ASTM D4541 pull-off adhesion test were conducted to quantify the interfacial adhesion strength between the deposited metal film and the polymer substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The Scotch (3M magic tape) tape test method was applied to investigate the adhesion strength of the metallized layers. 45 Besides, the ASTM D3359-02 standard tape test 46 and ASTM D4541 pull-off adhesion test 47 were conducted to quantify the interfacial adhesion strength between the deposited metal film and the polymer substrate. All the characterizations were performed at room temperature by considering n = 3 specimens for each characterization test.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[454] However, the major roadblock in implementing Parylene Cbased encapsulation is its poor adhesion with several substrates and metals commonly used in bioelectronics. [249,497] Techniques such as silanization, O 2 plasma treatment, mechanical interlocking, and annealing improve adhe sion and reduce risk of delamination between layers. [149,[498][499][500] LCP are a promising candidate for encapsulation materials because the high degree of crystallinity results confers excellent barrier properties.…”
Section: Flexible Polymers As Barrier Layersmentioning
confidence: 99%
“…Next, the effects of CF 4 treatment and scotch tape speed have been investigated by measuring force-displacement curves as shown in figure 5(a) [15]. It is found that (a) scotch tape velocity of 10 mm min −1 has made all metal debonded from polymer substrate with and without CF 4 treatment, while 1 mm min −1 has made partial metal debonding.…”
Section: Sample Preparationmentioning
confidence: 99%